PRINCIPLES OF SOCIAL COST-BENEFIT ANALYSIS OF PUBLIC ROAD PROJECTS FOLLOWED IN SOUTH AFRICA - Pienaar, Wessel (The South African Journal of Industrial Engineering, 2018)
This article discusses the most pertinent principles that underlie the preferred social cost-benefit analysis methodology to evaluate public road projects in South Africa. The ‘cost’ component of the analysis is the once-off investment cost sacrificed to establish a facility, and the ‘benefit’ component is the recurring reduction of disutility emanating from the operation, maintenance, and use of a facility. To determine future road-user benefits, the article develops a social surplus criterion that is termed ‘socio-economic user surplus’. A procedure is provided of the way that social cost-benefit analysis should be supplemented by the application of equity weighting, with a view to indicating both the expected allocative efficiency and distributive efficiency of a proposed road project. Lastly, the article discusses why the economic impacts that may stem from economically justified road projects are not considered in a social cost-benefit analysis.